Surgical management of retroperitoneal schwannoma complicated with severe hydronephrosis: A case report. Issue 39 (September 2018) - Zhang, Liandong; Gao, Ming; Zhang, Tongdian; Chong, Tie; Wang, Ziming; Liu, Wenpin; Li, Hecheng
Abstract: Rationale: Schwannomas are usually benign tumors arising from well-differentiated schwann cells, which rarely occur in the retroperitoneal space. The lack of specific signs and radiologic imaging characteristics makes preoperative diagnosis rather difficult. Most retroperitoneal schwannomas are benign and the primary treatment choice for retroperitoneal schwannomas is surgical excision, however, the involvement of the urinary system is scarcely reported. Patient concerns: A 34-year-old woman presented with progressive left abdominal pain and rebound abdominal mass at the left lower quadrant for 1 month. Radiological imaging suggested capsulated solid mass with cystic and necrotic areas in the retroperitoneum accompanied by severe left kidney hydronephrosis and preoperative biopsy result was inconclusive. Diagnoses: We believe this is a rare case of retroperitoneal schwannoma complicated with severe hydronephrosis. Interventions: After preparation, the patient underwent laparoscopy exploration and converted to open surgical exploration. The patient accepted complete surgical excision of the retroperitoneal tumor and left kidney. Postoperative pathology diagnosis of the mass was proven to be benign retroperitoneal schwannoma. Outcomes: Postoperative course of the patient was uneventful and the left abdominal pain was greatly improved. After 12-month follow up, no evidence of recurrence or any other complication including renal failure was observed. Lessons: Preoperative imaging and preoperative ultrasound-guided biopsy are helpful to make accurate diagnosis. The final diagnosis is based on postoperative histological and immunohistochemical findings. The primary treatment option is complete surgical resection of the retroperitoneal schwannoma and the involved upper urinary system when severe hydronephrosis occured. Local recurrence and overall survival are closely correlated with negative resection margins and pathology types.